Literature in the Dawn of Sociological Theory: Stories That Are Telling - MacMillen, Sarah Louise (Lexington Books, 2021)
Literature in the Dawn of Sociological Theory: Stories That Are Telling focuses on a selection of novelists from the early 1800s to the early 1900s and their connections to the insights of Classical Sociological Theory and the sociological imagination. This monograph also considers the aesthetic, sociological, and literary insights of Theodor Adorno, György Lukács, Fredric Jameson, Raymond Williams, Wolf Lepenies, Franco Moretti, Lucien Goldmann, and John Orr. The main chapters discuss the fiction of Nathaniel Hawthorne, Herman Melville, Joseph Conrad, Charlotte Perkins Gilman, Virginia Woolf, and Fyodor Dostoevsky. The concluding chapter reflects on the dawn of modernity, especially the birth of capitalism and the plague crisis via Boccaccio’s Florence, significant to The Decameron. Throughout the text, Sarah Louise MacMillen considers these “stories that are telling” in light of social issues today. She presents a case for highlighting the authors of the past, wherein these fictional accounts anticipate some of our contemporary social problems and social movements. These dynamics include the environmental crisis, the effects of globalization, Black Lives Matter, #MeToo, “cancel culture,” debates about gender nonconformity, and secularization. Finally, MacMillen reflects on the need for solidarity in shifting patterns of social existence and rebuilding post-COVID.